Computation of local permeability in gap-graded granular soils. Issue 1 (1st March 2022) - Annapareddy, V. S. R.; Sufian, A.; Bore, T.; Bajodek, M.; Scheuermann, A.
Abstract : This paper proposes semi-analytical methods to obtain the local permeability for granular soils based on indirect measurements of the local porosity profile in a large coaxial cell permeameter using spatial time-domain reflectometry. The porosity profile is used to obtain the local permeability using the modified Kozeny–Carman and Katz–Thompson equations, which incorporated an effective particle diameter that accounted for particle migration within the permeameter. The profiles of the local permeability obtained from the proposed methods are compared with experimentally obtained permeability distributions using pressure measurements and flow rate. The permeabilities obtained with the proposed methods are comparable with the experimentally obtained permeabilities and are within one order of magnitude deviation, which is an acceptable range for practical applications.